Assessment of aromatics to saturate ratios in three Niger Delta crudes - Chukwuemeka A. Nwadinigwe; Onyekachukwu K. Ezugwu; Alfreda O. Nwadinigwe (Egyptian Journal of Petroleum)
This study was designed to determine the aromatics to saturate ratios in three Nigerian Niger Delta crude oils to ascertain the crude oil source with the highest asphaltene risk. Three crude oil samples were collected from different locations: Kokori, Afiesere and Nembe in the Niger Delta region, Nigeria. The physical properties of the crudes (viscosity, density, API gravity) were determined. Saturates, aromatics, resins, asphaltenes (SARA) fractionation method was employed to separate different components in the crude oil. The composition and concentration of the saturates and aromatics hydrocarbon fractions were determined using a gas chromatograph. Results showed that API gravities ranged from 34° to 39° indicating that the three crudes are light. n-Heptane precipitation showed that Kokori crude had the highest weight percent concentration of asphaltenes (2.33%) and Afiesere crude, the least (1.91%). The gas chromatographic analysis of the saturates and aromatics showed that the total concentrations (mg/L) of all the saturates in Kokori, Afiesere, and Nembe were 871.26, 885.56, and 780.21 respectively while the total concentration of all the aromatics in the crudes were 80.15, 89.73 and 75.11 respectively. The aromatics to saturate ratios were computed and the results showed that this ratio decreased in the order Kokori crude < Nembe crude < Afiesere crude. This implies that Kokori crude with the lowest ratio will cause most asphaltene deposition problems than the other crudes.